Lipid status and carotid intima-media thickness in patients with end-stage renal disease - Damir Rebić; Edin Begić; Armin Šljivo; Nermir Granov; Senad Hasanspahić; Alen Džubur; Azra Durak-Nalbantić (Medicinski glasnik, 2023)
Aim: To assess morphological characteristics of carotid blood vessels in uremic patients before to the initiation of the dialysis treatment, and corelate data with various dialysis therapy modules. Methods: The study included 30 patients with end-stage renal disease (ERDS) prior to commencing dialysis, 30 patients treated with haemodialysis and 30 patients treated with continuous ambulatory peritoneal dialysis. The control group consisted of 15 subjects with normal kidney function (eGFR>60ml/min). Carotid intima-media thickness (CIMT), as well as lipid status values (cholesterol, triglycerides, low-density lipoprotein (LDL), high-density lipoprotein (HDL), apolipoprotein A, apolipoprotein B) were evaluated. Results: The significant difference in CIMT was detected between the control and haemodialysis groups (p<0.001), and between the control and the peritoneal dialysis group (p=0.004). In patients in the predialysis group, CIMT was influenced by cholesterol (p=0.013), HDL (p=0.044), LDL (p=0.001) and ApoB (p=0.042) values. A significant difference in CIMT was proved between the haemodialysis and predialysis group of patients (p<0.001). The only variable from the patient's lipometabolic profile significantly associated with the change in IMT in uremic patients was HDL. A significant difference was found in the average value for systolic blood pressure (p<0.001) and diastolic blood pressure (p=0.018) in patients before starting the dialysis treatment compared to patients treated with other dialysis methods. Conclusion: Patients on haemodialysis treatment had a significantly greater CIMT, which is in relation with a higher cardiovascular risk.
Keywords: atherosclerosis; kidney failure; prognosis